Exploring the relevance of the type of horizontal separator to optimize the extraction efficacy for the Arbequina variety - Boudebouz, Abdelaziz; Hermoso, Juan-F; Martí, Esteve; Ninot, Antonia; Boqué, Ricard; Mestres, Montserrat; Aceña, Laura; Veneziani, Gianluca; Selvaggini, Roberto; Servili, Maurizio; Romero, Agustí (Frontiers in Plant Science, 2024)
The productivity of virgin olive oil depends not only on agronomic factors but also on the technological factors of the extraction process. Is a matter of fact that 'Arbequina' variety use to have extractability problems, that is a challenge for the master millers anywhere. This work aims to evaluate the behavior of different decanters and seeks to modulate the effect of some processing parameters and their interactions with oil extraction efficiency in the case of 'Arbequina'. Fruit characteristics, processing parameters and extractability were collected over 10 years from 38 decanters that belong to 5 different brands. The results have shown that fruit moisture is the most relevant factor for oil extractability, especially over 52%. Furthermore, extractability is positively correlated with malaxing temperature, addition of water and total fat content in the fruit. However, the results show that before applying a regulation, the type of decanter must be considered. The model used in this study has allowed to optimize the regulations for each type of decanter to reduce oil losses within pomace, achieving an extraction efficiency within the range 78% -91,5%. In fact, the best extraction efficiency results (91.5%) were obtained by processing at temperatures >26ºC and water injection (5%).